Livestock, capture fisheries, and aquaculture: Status and recent trends - Belton, Ben; Fang, Peixun (International Food Policy Research Institute, 2024)
Livestock rearing and fishing have been central components of rural livelihoods in Myanmar for centuries and remain so today. More capital-intensive forms of marine fishing, aquaculture, and poultry farming began to expand during the early 1990s and have grown briskly since then. Poultry and aquaculture commoditization accelerated between 2011 and 2019, stimulated by the demand-side pull of rapid income growth and by foreign and domestic investment in areas such as feed milling and food retail (for example, businesses such as Kentucky Fried Chicken, which opened in Myanmar in 2015). However, despite recent growth, both sectors lag behind those in more developed countries in the region in technological sophistication, scale, and regulation.